3.3=-16t2+73.3+5.5

Rewrite the equation as -16t2+73.3+5.5=3.3.

-16t2+73.3+5.5=3.3

Add 73.3 and 5.5.

-16t2+78.8=3.3

Subtract 78.8 from both sides of the equation.

-16t2=3.3-78.8

Subtract 78.8 from 3.3.

-16t2=-75.5

-16t2=-75.5

Divide each term in -16t2=-75.5 by -16.

-16t2-16=-75.5-16

Cancel the common factor of -16.

Cancel the common factor.

-16t2-16=-75.5-16

Divide t2 by 1.

t2=-75.5-16

t2=-75.5-16

Divide -75.5 by -16.

t2=4.71875

t2=4.71875

Take the square root of both sides of the equation to eliminate the exponent on the left side.

t=±4.71875

First, use the positive value of the ± to find the first solution.

t=4.71875

Next, use the negative value of the ± to find the second solution.

t=-4.71875

The complete solution is the result of both the positive and negative portions of the solution.

t=4.71875,-4.71875

t=4.71875,-4.71875

The result can be shown in multiple forms.

Exact Form:

t=4.71875,-4.71875

Decimal Form:

t=2.17226839…,-2.17226839…

Solve for t 3.3=-16t^2+73.3+5.5